OPTIMIZATION OF OIL OBTAINED IN B FIELD M LAYER X BLOCK WITH RESERVOIR SIMULATION - Bianca Marella Putri Salusu; Sugiatmo Kasmungin; Andry Prima (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2018)
There are a lot of mature fields in Indonesia that have been produced since a long time ago. B Field is one of the mature fields in Indonesia that is still producing until today. Up till now, in B field has been drilled 570 wells with 55 prospects layers. The production of B Field that has been done since 1931 affects the pressure drop in this field. This drop in pressure also led to a decrease in production in the field. To increase the recovery factor in the field, production forecast is done by using reservoir simulation method. In the reservoir simulation process, some injection scenarios planning are done as alternatives to know which scenario gives the most optimum oil production. The reservoir simulation process includes the data preparation, reservoir modeling, initialization, history matching, field development simulation scenarios, and injection rate sensitivity. There are three scenarios applied to find the most optimum recovery method in M Layer through reservoir simulation. Out of the three scenarios that have been done, the Author proposes scenario III as the best scenario because it gives the highest cumulative value of oil production.